Fatores prognósticos associados a sobrevida de pacientes submetidos a hemodiálise em uma unidade hospitalar - Vasconcelos, Jardel Martins de (2018)
Introduction: Hemodialysis treatment is a therapeutic alternative in reversing the clinical metabolic decompensation of patients with renal insufficiency. The time elapsed between hospital admission and initiation of hemodialysis is determinant in the prognosis of the patient. Thus, late onset hemodialysis may influence the length of hospital stay, number of required hemodialysis sessions, hemodynamic stability, and outcome. Objective: To analyze the prognostic factors associated with the specific survival of patients submitted to hemodialysis (HD) in a hospital unit. Methodology: The research was approved by the human ethics committee with the number of opinion 2,434,202. This is an observational retrospective cohort study of patients undergoing hemodialysis in the period 2016-2017 at Hospital University of Lagarto (HUL) in Sergipe (SE). The sample consisted of the medical record of all the patients who were attended by the hospital HD service that met the inclusion and exclusion criteria during the proposed period. Data were described by means of mean and standard deviation and absolute and relative percentage frequency. Categorical associations were tested using the Chi-Square test. The differences of position measurement were used the Mann-Whitney test. Survival curves were estimated using the Kaplan-Meier method and the differences tested by the Log-Rank test and the Log-Rank test with Dunn-Sidak correction for multiple comparisons. Gross and adjusted risk ratios were estimated using Cox regression. The level of significance was set at 5%. Results: Of the 129 charts analyzed, the majority (n= 88, 68.2%) were older than 60 years and males (n= 76, 58.9%). She presented a longer stay of hospitalization between 8 and 30 days (n= 71; 55%). Early onset of HD (n= 68; 52.7%) with time ≤ 3 days after admission (ADM). Most performed up to 3 HD sessions (n= 48, 37.2%). Patients with acute CKD had a higher prevalence with (n= 53; 41.1%) of the sample. When considering the outcome, it was possible to observe that the onset of HD within 3 days after ADM presented an average survival time (TM) of 69.7 (53.1-86.3) days. TM was higher in patients with acute chronic renal failure (CKD) with 61.9 (46.5-77.4) days. Both the time elapsed between ADM and the onset of HD between 4 to 9 days of ADM and the diagnosis of AKI were more likely to occur at any time of treatment with an RRa of 5.96 (2.35 -15.16) and 4.27 (1.69-7.16), respectively. Those who did up to three HD sessions had an RR of 34.19 (12.63-92.56). Conclusion: The early diagnosis of renal failure and referral to the HD service are determining factors in the average survival time and in the probability of death. Therefore, it is necessary to adopt more effective monitoring measures, with the intention of immediately initiating the HD, guaranteeing an improvement in the patient's prognosis.